THE PAPAR TRADITION IN THE CUSTOM ON DEATH IN TEUPAH TENGAH SUBDISTRICT, SIMEULUE REGENCY - Sri Rahayu Nengsih Ainun; Aslam Nur (Indonesian Journal of Islamic History and Culture, 2021)
This article is entitled "The Papar Tradition in the Custom on Death in Teupah Tengah Subdistrict, Simeulue Regency". The purpose of this research is to examine the history of papar tradition in Simeulue, reasons among the people who perform or not perform the tradition, to find out meanings and symbols contained in the papar tradition, and to understand the perception of the community and scholars to the papar tradition. This study applies a qualitative method. This method is used to explore sources of information and data in the form of interviews and documentation. The research results show that the Papar Tradition has existed from the time of ancestors to the present. In the Papar tradition, there are several processes carried out, namely, the Sarak Papar process: Sarak is the delivery, while the Papar is the details; the Manjalang Tuaik Faten process means inviting relatives, the Mangatuk Lulumang process means informing all invitees that the family no longer have a father. Mangameleng process means to return, process of Manidau means to restore.